2018
DOI: 10.2139/ssrn.3149323
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Big Data on Recommendation Quality. The Example of Internet Search

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…See for example Susarla (2019). Schaefer et al (2018), on the other hand, find that the quality of search results does improve in the presence of more data on previous searches with personalized information playing a critical role. This literature is also related to the studies which analyze the value of cookies and personalization such as those by Miller and Skiera (2017) and Johnson et al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…See for example Susarla (2019). Schaefer et al (2018), on the other hand, find that the quality of search results does improve in the presence of more data on previous searches with personalized information playing a critical role. This literature is also related to the studies which analyze the value of cookies and personalization such as those by Miller and Skiera (2017) and Johnson et al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…This paper employs a game theoretic model to study and compare the effect of data sharing as well as data siloing on competition, innovation and welfare. Thereby, we contribute to the emerging literature analyzing the economic effects of data-driven network effects (e.g, Gregory et al, 2020;Haftor et al, 2021;Argenton and Prüfer, 2012;Schaefer et al, 2018), and the associated regulation of digital platforms (see, e.g., Hagiu and Wright, 2020;Prüfer and Schottmüller, 2020;Parker et al, 2021;Tucker, 2019;Kraemer and Schnurr, 2021). We build on prior research that has shown that data-driven network effects can be a powerful source of market power and dominance (Schaefer et al, 2018;Prüfer and Schottmüller, 2020), and that access to large data sets and improved predictions can boost innovation (e.g., Agrawal et al, 2018;Bajari et al, 2019).…”
Section: Introductionmentioning
confidence: 98%
“…Data-driven network effects are an indirect network effect that constitutes a virtuous cycle as follows: The use of a data-driven service (or product) generates more data, which is the basis for improved algorithmic learning and data analytics, which then allows to further improve the data-driven service, and which then ultimately increases demand, which in turn generates even more data, and so on and so forth. The prime example of a service with strong data-driven network effects is a search engine (Argenton and Prüfer, 2012;Schaefer et al, 2018). As more consumers use the search engine, more click and query data is collected allowing the search engine to improve its search algorithm, thereby drawing in more consumers, which creates even more click and query data.…”
Section: Introductionmentioning
confidence: 99%
“…Such arguments motivate research on how data influences firm dynamics [Farboodi et al (2019), Farboodi and Veldkamp (2021)] and how it disproportionally benefits large firms [Begenau et al (2018)], which then stimulates debates on the implication of AI and, more precisely, data on competition [Crémer et al (2019),De Corniere and Taylor (2020), Lambrecht and Tucker (2015), Newman (2014), Petit (2017), Rubinfeld and Gal (2017)]. Of course, the degree to which data impacts business value and hence the competition varies with the design parameters like the degree of personalization [Holtz et al (2020), Schaefer et al (2018)] or the externalities between recommendation clusters [Bajari et al (2018)]. Nevertheless, studying the effect of data's time dependency on competition remains crucial.…”
Section: Introductionmentioning
confidence: 99%